Political Power and Social Theory. - Go, Julian (Political Power and Social Theory, 22., 2011)
This volume of Political Power and Social Theory will be among the first to critically assess the meanings of race and religion in America under the Obama administration, and features controversial chapters by Phil Gorksi of Yale University and Eduardo Bonilla-Silva of Duke University, among others.